Дослідження температурних полів по товщині футерівки і висоті ковша під час сушіння і розігріву сталерозливних ковшів з різною футерівкою - Плохіх, П.А.; Хавалиць, Ю.В.; Плохіх, П.А. (Physico-technological Institute of Metals and Alloys, 2023)
The purpose of this work is to determine the temperature distribution of the lining of steel-teeming ladles both in the height of the ladle and in the thickness of the lining in its different horizons during drying and heating of the ladle. For research, steelpouring ladles no. 7 and no. 18 were taken into operation, the lining of which was made of mullite-alumina mass (MMK-65) and the ladle no. 13 with periclase-lime lining.